Ctirad and Šárka. Comparative analysis of selected aspects of the style of historical epics by Jaroslav Vrchlický and Julius Zeyer - Schacherl, Martin (Bohemistyka, 2024)
The aim of the paper is a comparative analysis of selected aspects of the singular styles of the historical epics Šárka by Jaroslav Vrchlický (1853–1912) and Ctirad Julius Zeyer (1841–1901); classical authors of Czech literature from the so-called Lumira generation of the second half of the 19th century. The juxtaposition of thematically similar texts allowed for a more pronounced identification of the characteristic features of the singular styles of both poets, possibly the specificity of their historical and mythic epic poetry, ideally the stylistic dominance of the authorial styles of Jaroslav Vrchlický and Julius Zeyer in mutual comparison. In order to achieve the set objectives, the methods of comparative and mathematical stylistics were used.